2016
DOI: 10.1371/journal.pgen.1006327
|View full text |Cite|
|
Sign up to set email alerts
|

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease

Abstract: We performed an exome-wide association analysis in 1393 late-onset Alzheimer’s disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5–15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 57 publications
4
65
0
Order By: Relevance
“…Other than the well-established coding variants (p.C112R and p.R158C) in APOE (APOlipoprotein E , OMIM #104310)[431433], however, the significance of most of these variants awaits to be experimentally verified. Through a recent exome-wide association study, the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium[434,435] identified a rare coding variant in a previously uncharacterized gene that has a strong effect size on LOAD[436]. A P155L variant in TM2D3 (TM2 domain containing 3) was associated with a ~7.5 fold chance of developing LOAD and a 10-year earlier age of onset in an Icelandic population.…”
Section: Using Drosophila To Study Rare Functional Variants In Genes mentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the well-established coding variants (p.C112R and p.R158C) in APOE (APOlipoprotein E , OMIM #104310)[431433], however, the significance of most of these variants awaits to be experimentally verified. Through a recent exome-wide association study, the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium[434,435] identified a rare coding variant in a previously uncharacterized gene that has a strong effect size on LOAD[436]. A P155L variant in TM2D3 (TM2 domain containing 3) was associated with a ~7.5 fold chance of developing LOAD and a 10-year earlier age of onset in an Icelandic population.…”
Section: Using Drosophila To Study Rare Functional Variants In Genes mentioning
confidence: 99%
“…Since the variant amino acid (p.P155) is not conserved between human and Drosophila , we humanized the fly amx gene by generating a genomic rescue construct in which the fly amx coding region has been replaced by the human sequence. Interestingly, the reference TM2D3 was able to partially rescue the neurogenic phenotype and lethality of the maternal amx mutant embryos, whereas TM2D3 with the p.P155L variant was not able to do so[436]. Hence, p.P155L associated with LOAD was shown to be a functional variant based on Notch-signaling related phenotypic assay performed in vivo , and further functional studies are ongoing to determine the precise molecular function of TM2D3/Amx in vivo .…”
Section: Using Drosophila To Study Rare Functional Variants In Genes mentioning
confidence: 99%
“…Sequencing in a multiply-affected family found a rare, missense variant in TTC3 that was shared in all affected members of the family [64]. A rare variant in the gene TM2D3 was enriched in Icelanders with LOAD and identified as a functionally damaging allele [65]. Two variants in tight linkage disequilibrium in AKAP9 were found to be associated with LOAD in African Americans [66].…”
Section: Gwasmentioning
confidence: 99%
“…For example, the functional impact of a rare TM2D3 human variant that was predicted to be non-pathogenic was identified in association with late onset AD susceptibility [64]. The loss of the fly homologue of TM2D3 , almondex ( amx ), is known to cause embryonic lethality and severe neurogenic defects.…”
Section: Introductionmentioning
confidence: 99%